Nanomodified Switch Induced Precise and Moderate Activation of CAR‐T Cells for Solid Tumors (Adv. Sci. 12/2023). Issue 12 (26th April 2023) - Wang, Xinyue; Meng, Fanyan; Li, Xiang; Xue, Luxin; Chen, Anni; Qiu, Yuling; Zhang, Zhifan; Li, Lin; Liu, Fengcen; Li, Yishan; Sun, Zhichen; Chu, Yanhong; et al.
Abstract : Cancer Immunotherapy In article number 2205044, Baorui Liu, Rutian Li, and co‐workers constructed gelatinase‐responsive NanoSwitch to control the activation process of CAR‐T cells, leading to on‐site activation of CAR‐T cells at the tumor region in a sustainable way. This platform has promising potential to prevent the main obstacles in the CAR‐T therapy for solid tumors including cytokine‐release syndrome and on‐target/off‐tumor toxicity.